A pyrrole-containing hydrazone and its Cu2+ complex: an easily accessible optical chemosensor system for the successive detection of Zn2+/Cu2+ and pyrophosphate. Issue 48 (26th November 2018) - Wang, Yang; Hou, Xufeng; Li, Zhensheng; Zhou, Qihang; Lei, Mengmeng; Hu, Shanshan; Wu, Xiaopei; Li, Chenming; Xu, Zhihong; Wang, Yuan
Abstract : A simple chemosensor, namely, ethyl 5-(isonicotinoylimino)methyl-2, 4-dimethyl-pyrrole-3-carboxylate (1 ), was synthesized and characterized. Abstract : A simple chemosensor, namely, ethyl 5-(isonicotinoylimino)methyl-2, 4-dimethyl-pyrrole-3-carboxylate (1 ), was synthesized and characterized. Probe1 exhibited great selectivity when used as an off–on fluorescent sensor for Zn 2+ . Moreover, 1 can be used as a colorimetric probe for the detection of Cu 2+ in semiaqueous media. The putative binding mechanism of1 with its target analytes was confirmed through UV-Vis absorption analysis, fluorescence measurements, mass spectroscopy, 1 H NMR analysis, and density functional theory calculations. In addition, the resulting1 + Cu 2+ complex can be used as a colorimetric sensor for pyrophosphate. Probe1 is successfully applied in monitoring intracellular Zn 2+ in the glioma cell line U251.